The role of internalized homonegativity in the faith and psychological health of lesbians. Issue 4 (2nd October 2017) - Whicker, Dane R.; de St. Aubin, Ed; Skerven, Kim
ABSTRACT: Among lesbians, faith-based beliefs and behaviors may be associated with negative psychological health due to the interplay between religious and sexual identities. The present study examined health outcomes, faith-based beliefs (views of God as loving and controlling), faith-based behaviors (personal spiritual practices, religious activities), and internalized homonegativity in a sample of 225 self-identified lesbians. We hypothesized that internalized homonegativity would moderate the relationship between health outcomes and faith-based beliefs and behaviors among lesbians. Generally, results indicated that some faith-based beliefs and behaviors were related to negative health outcomes among lesbians with higher levels of internalized homonegativity, but among those with lower levels of internalized homonegativity, the negative associations with health were mitigated.